COMPARASI PENGALIHAN HARTA HIBAH MENJADI HARTA WARISAN PERSPEKTIF KOMPILASI HUKUM ISLAM DAN KITAB UNDANG-UNDANG HUKUM PERDATA - Dermina Dalimunthe (Institut agama islam negeri Padangsidimpuan, 2020)
Comparation of the transfer of grant assets is inherited from the perspective of KHI and the Civil Code, in the KHI the process of transferring the grant assets automatically becomes inheritance whereas according to the Civil Code through the inbreng process. justice and protect the portion of the heirs established by the KHI and the Civil Code